Safe and effective medical management of pain for people with rheumatoid arthritis: Current evidence, patient perspectives, and person-centred deprescribing - Lisa Vizza; Sujita W. Narayan; Peter Youssef; Rowena Ivers; Matthew Youssef; Alexander Youssef; Rachel Thompson; Christina Abdel Shaheed (Health Literacy and Communication Open, 2025)
Rheumatoid arthritis (RA) is a condition that causes joint inflammation and affects ∼19 million adults globally. Pharmacological management can include a combination of disease-modifying antirheumatic drugs (DMARDs) and pain medicines. Where the response to DMARDs has been good, pain medicines may no longer provide additional benefits and a deprescribing plan may be appropriate. Consideration of the attitudes and acceptability of deprescribing pain medicines in people with RA is important, alongside a communication strategy that can support informed decision-making, particularly as one in seven adults with RA have low health literacy. This commentary synthesised the evidence on the benefits and harms of common analgesics used in people with RA to guide patient and clinician decision making. We explored the communication needs of people with RA, and drew upon the pain literature, to provide practical guidance to support dialogue between patients and clinicians about effective pain management and deprescribing of pain medicines in people with RA. We provided directions for future research to improve outcomes for people with RA, particularly those with low health literacy who may want or need to engage in a deprescribing plan.